Tackling Quantitation: A Report on the Annual Spring Workshop of the HUPO-PSI - Orchard, Sandra; Jones, Andrew; Albar, Juan-Pablo; Cho, Sang Yun; Kwon, Kyung-Hoon; Lee, Cheolju; Hermjakob, Henning (WILEY-V C H VERLAG GMBH, 2010)
The annual Spring Workshop of the HUPO-PSI took place in Korea, where the Mass Spectrometry and Protein Separations groups joined forces to tackle the issue of the consistent reporting of quantitative proteomic data generated by mass-spectrometry-based technologies. A preliminary mzQuantML schema was drafted which, when completed and tested, will complement the existing mzIdentML schema for reporting protein identifications. The Molecular Interactions group concentrated on the implementations of the PSICQUIC (PSI Common Query InterfaCe) service that allows users to simultaneously query interaction data across multiple participating resources. Work was also undertaken to update the MIAPE guidelines, in response to feedback from the editors of a number of proteomic journals.
Keywords: IDENTIFICATION